Q.No.6. E is the mid-point on median AD of AABC. (See given figure) Show that;
ar(DEC) = -ar(ABC)
Answers
Answered by
2
Step-by-step explanation:
given:-
AD is the median of ΔABC and E is the midpoint of AD
Through D draw DG∣∣BF
In ΔADG
E is the midpoint of AD and EF∣∣DG
By converse of midpoint theorem we have
F is midpoint of AG and AF=FG ..............1
Similarly, in ΔBCF
D is the midpoint of BC and DG∣∣BF
G is midpoint of CF and FG=GC ..............2
From equations 1 and 2
we will get
AF=FG=GC........3
AF+FG+GC=AC
AF+AF+AF=AC ......... from eq 3
AF=AC
AF=(1/3)AC
Similar questions